Anti-Cancer Stem-like Cell Compounds in Clinical Development – An Overview and Critical Appraisal - Marcucci, Fabrizio; Rumio, Cristiano; Lefoulon, François (Frontiers in Oncology, 2016)
Cancer stem-like cells (CSC) represent a subpopulation of tumor cells with elevated tumor-initiating potential. Upon differentiation, they replenish the bulk of the tumor cell population. Enhanced tumor-forming capacity, resistance to antitumor drugs, and metastasis-forming potential are the hallmark traits of CSCs. Given these properties, it is not surprising that CSC have become a therapeutic target of prime interest in pharmacological research. In fact, over the last few years an enormous number of articles describing compounds endowed with anti-CSC activities have been published. In the meanwhile, several of these compounds and also approaches that are not based on the use of pharmacologically active compounds (e.g. vaccination, radiotherapy), have progressed into clinical studies. This article gives an overview of these compounds, proposes a tentative classification, describes their biological properties and their developmental stage. To conclude, we discuss the optimal clinical setting for using these compounds, the need for biomarkers allowing patient selection, the redundancy of CSC signaling pathways and, consequently, the utility of employing combinations of anti-CSC compounds and, eventually, the therapeutic limitations posed by the plasticity of CSCs.